Risk factors for hemoptysis complicating 17-18 gauge CT-guided transthoracic needle core biopsy: multivariate analysis of 249 procedures - Guillaume Chassagnon; Jules Gregory; Marc Al Ahmar; Pierre Magdeleinat; Paul Legmann; Joel Coste; Marie Pierre Revel (Diagnostic and Interventional Radiology, 2017)

(untitled)
Purpose:We aimed to identify modifiable and nonmodifiable risk factors for hemoptysis complicating computed tomography (CT)-guided transthoracic needle biopsy.Methods:All procedures performed in our institution from November 2013 to May 2015 were reviewed. Hemoptysis was classified as mild if limited to hemoptoic sputum and abundant otherwise. Presence of intra-alveolar hemorrhage on postbiopsy CT images was also evaluated. Patient- and lesion-related variables were considered nonmodifiable, while procedure-related variables were considered modifiable.Results:A total of 249 procedures were evaluated. Hemoptysis and alveolar hemorrhage occurred in 18% and 58% of procedures, respectively, and were abundant or significant in 8% and 17% of procedures, respectively. Concordance between the occurrence of significant alveolar hemorrhage (grade ≥2) and hemoptysis was poor (κ=0.28; 95% CI [0.16–0.40]). In multivariate analysis, female gender (P = 0.008), a longer transpulmonary needle path (P = 0.014), and smaller lesion size (P = 0.044) were independent risk factors for hemoptysis. Transpulmonary needle-path length was the only risk factor for abundant hemoptysis with borderline statistical significance (P = 0.049).Conclusion:The transpulmonary needle path should be as short as possible to reduce the risk of abundant hemoptysis during CT-guided transthoracic needle biopsy.